PERANCANGAN SISTEM INFORMASI ADMINISTRASI PEMELIHARAAN PESAWAT TERBANG MILITER PADA SKADRON TEKNIK (SKATEK) 021 - ., Indarwati; Sinaga, Dimpo (Universitas Dirgantara Marsekal Suryadarma, 2017)
Advances in information technology, access to data or information available can take place quickly, efficiently and accurately. The rapid technological developments have enabled the air media widely for various purposes and created a new force known as air power.According to the doctrine of air power, air control air capability, air attack, air support with various modifications according to the needs and needs of each country. Aircraft that require air power of various types, types and functions is the type of hunter / combat aircraft, reconnaissance, bombers, and transport aircraft.What can be done to transport personnel and equipment such as weaponry in the soonest possible time. In the context of Scheduling, speed and accuracy. Measurement tool readiness unit operation unit.